2004
DOI: 10.1074/jbc.m407694200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Escherichia coli MoaB Suggests a Probable Role in Molybdenum Cofactor Synthesis

Abstract: The crystal structure of Escherichia coli MoaB was determined by multiwavelength anomalous diffraction phasing and refined at 1.6-Å resolution. The molecule displayed a modified Rossman fold. MoaB is assembled into a hexamer composed of two trimers. The monomers have high structural similarity with two proteins, MogA and MoeA, from the molybdenum cofactor synthesis pathway in E. coli, as well as with domains of mammalian gephyrin and plant Cnx1, which are also involved in molybdopterin synthesis. Structural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Structural analysis of MoaB proteins demonstrated that MoaB hexamers are formed by dimerization of trimers [9], [10]. Catalytically active, trimeric MPT-adenylyl-transferases were identified in mesophilic organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Structural analysis of MoaB proteins demonstrated that MoaB hexamers are formed by dimerization of trimers [9], [10]. Catalytically active, trimeric MPT-adenylyl-transferases were identified in mesophilic organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, we did not detect any change in HAP- or chlorate-sensitivity in the Δ mogA strains carrying moaB- overexpressing vectors (Table 2), clearly indicating that MoaB cannot substitute for MogA. Based on the ability of MoaB protein to bind GTP and, presumably, other intermediates of Moco biosynthesis (Sanishvili et al, 2004), it has been proposed that MoaB may play a yet unknown regulatory role in the Moco biosynthesis pathway, for example, by sensing the Moco status in cell (Bevers et al, 2008) or functioning as a Moco transporting/storage protein (Sanishvili et al, 2004). It has also been proposed that MoaB and MogA might form functional hetero-oligomers (Sanishvili et al, 2004).…”
Section: Resultsmentioning
confidence: 76%
“…Both the primary sequence and crystal structure of MoaB show strong similarities with the MogA protein (Bader et al, 2004; Bevers et al, 2008; Sanishvili et al, 2004), which catalyzes formation of the MPT-AMP intermediate during the Mo-insertion step into Moco. Indeed, in the archaeon Pyrococcus furiosus , which lacks a MogA protein, its MoaB enzyme is responsible for the MPT adenylylation (Bevers et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomes of P. horikoshi and many related thermophiles lack MogA but instead they all contain MoaB, a protein of unknown function with high Sanishvili et al (2004) have assumed that due to its genomic localization E. coli MoaB participates in cPMP synthesis (step 1) and consequently they showed a weak GTP binding and hydrolysis. However, it is known that cPMP synthesis is only dependent on MoaA and MoaC (Hänzelmann and Schindelin 2004).…”
Section: Bis-mpt Cofactors With Tungstenmentioning
confidence: 99%